(untitled) - Chichester Clark, Emma (New York, 1999)
When Lily's relatives give her lots of new stuffed animals, Blue Kangaroo fears that he will be replaced in her affections.
"First published in Great Britain"--verso t.p.
Accelerated Reader AR